IFN-γ and TNF-α synergism may provide a link between psoriasis and inflammatory atherogenesis. Issue 1 (December 2017) - Mehta, Nehal; Teague, Heather; Swindell, William; Baumer, Yvonne; Ward, Nicole; Xing, Xianying; Baugous, Brooke; Johnston, Andrew; Joshi, Aditya; Silverman, Joanna; Barnes, Drew; Wolterink, Liza; et al.
Abstract Chronic inflammation is a critical component of atherogenesis, however, reliable human translational models aimed at characterizing these mechanisms are lacking. Psoriasis, a chronic inflammatory skin disease associated with increased susceptibility to atherosclerosis, provides a clinical human model that can be utilized to investigate the links between chronic inflammation and atherosclerosis development. We sought to investigate key biological processes in psoriasis skin and human vascular tissue to identify biological components that may promote atherosclerosis in chronic inflammatory conditions. Using a bioinformatics approach of human skin and vascular tissue, we determined IFN-γ and TNF-α are the dominant pro-inflammatory signals linking atherosclerosis and psoriasis. We then stimulated primary aortic endothelial cells andex-vivo atherosclerotic tissue with IFN-γ and TNF-α and found they synergistically increased monocyte and T-cell chemoattractants, expression of adhesion molecules on the endothelial cell surface, and decreased endothelial barrier integrityin vitro, therefore increasing permeability. Our data provide strong evidence of synergism between IFN-γ and TNF- α in inflammatory atherogenesis and provide rationale for dual cytokine antagonism in future studies.